Mesoscale spatio-temporal variability of airborne lidar-derived aerosol properties in the Barbados region during EUREC4A - P. Chazette; A. Baron; A. Baron; C. Flamant (Atmospheric Chemistry and Physics, 2022)
From 23 January to 13 February 2020, 20 ATR-42 scientific flights were conducted in the framework of the EUREC4A field campaign over the tropical Atlantic, off the coast of Barbados (13∘30′ N, −58∘30′ W). By means of a sideway-pointing lidar, these flights allowed us to retrieve the optical properties of the aerosols found in the sub-cloud layer and below the trade wind inversion. Two distinct periods with significant aerosol contents were identified in relationship with the so-called trade wind and tropical regimes, respectively. For these two regimes, mixings of two air mass types encompassing dust and carbonaceous aerosols have been highlighted. Both were mainly from West Africa with similar optical contributions and linked to dust uptake above Sahara and biomass burning between Guinea-Bissau and Côte d'Ivoire. In the tropical transport regime, the wind within the planetary boundary layer is stronger and favours a contribution of marine aerosols (sulfate and sea salt aerosol components) in shallower aerosol layers than for the trade wind transport regime. The latter is responsible for advecting dust–biomass-burning-aerosol mixtures in the deeper, well-mixed layer, in part due to the complex interactions of the easterly flow from West Africa with mid-latitude dynamics. The aerosol vertical structures appear to be well reproduced using atmospheric composition reanalyses from CAMS when comparing with lidar-derived vertical profiles. The competition between the two types of transport regimes leads to strong heterogeneity in the optical properties of the horizontal aerosol field. Our study highlights the transport regime under which a significant mixture of dust and biomass burning aerosols from West Africa can be observed over the Caribbean and Barbados in particular, namely the trade wind regime.